In situ, high-resolution evidence of metals at the sediment-water interface under ice cover in a seasonal freezing lake - Yuan, Yuxiang; Wang, Qichen; Dong, Xiangqian; Zhu, Yinze; Wu, Zhong; Yang, Qian; Zuo, Yunjiang; Liang, Shuang; Wang, Chunqing; Zhu, Xiaoyan (Frontiers in Ecology and Evolution, 2022)
Ice cover in winter as a physical barrier and duration would profoundly impact on changes in endogenous metal loading, migration, and transformation. Although a gradual reduction in duration and occurrence of lake ice cover in boreal lake ecosystems has been confirmed, little attention tothe ice-covered period is received compared to open water studies. In this study, novel-developed diffusive gradients in thin films (DGT, ZrO-Chelex) probes were deployed to obtain the in-situ and high-resolution information on metals (Cu, Zn, Pb, Mn, Cd, Cr, and As) at the sediment-water interface (SWI) in a seasonal ice-covered lake, Chagan Lake (CL). In addition, each metal's "source-sink" characteristics related to their endogenous release were determined based on Fick 's first law. Concentrations of labile metals at the SWI demonstrated significant spatial heterogeneity, peaking just below the sediment-water interface. Compared with other similar studies, concentrations of Pb (0.55 µg/L), Cr (0.58 µg/L) and As (2.4 µg/L) were a little higher even under-ice than in other freshwater rivers and lakes, indicating potential pollution due to agricultural intensification and petroleum extraction. The apparent diffusive fluxes suggested that sediments acted as a sink for Pb (-0.01 mg m-2 d-1), Cr (-2.37 mg m-2 d-1), and Cd (-0.1 mg m-2 d-1), from the overlying water into the sediment, while Cu (0.12 mg m-2 d-1), Zn (0.75 mg m-2 d-1), Mn (15.89 mg m-2 d-1), and As (2.12 mg m-2 d-1) as a source from sediments into the overlying water. Dissolved oxygen was the principal factor (79.5%, P= 0.032), determining the variation of the available metals at the SWI. As the urgent need for improving the cognitive of lake ecology under ice, this study addressed the previously unknown behavior of the labile metals at the SWI and provided a unique insight into lake management during the ice-cover periods when external nutrient input was cut off.